ETNOMATEMATIKA: ARSITEKTUR RUMAH ADAT DI SUKABUMI SEBAGAI BAHAN PEMBELAJARAN MATEMATIKA DI PENDIDIKAN DASAR - Imswatama, Aritsya; Zultiar, Indra (Institut Agama Islam Negeri Curup, 2019)
This study aims to describe matters relating to mathematics in the architecture of traditional houses in Sukabumi. This type of research is a qualitative research with an ethnographic approach. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis techniques used are data reduction, data display, verification and inference. The results of this study indicate that in the architecture there are mathematical elements including geometry consisting of rectangles, squares, and lengths. The results of this study are expected to be used as an innovation in mathematics learning in elementary schools.